Critical Point Analysis and Improvement Strategies for Demersal Fish Handling in the Seribu Islands - Vivi Septi Sari; Mustaruddin Mustaruddin; Fis Purwangka (Jurnal Ilmu Pertanian Indonesia, 2026)
The handling of demersal fish in the Seribu Islands faces major challenges related to quality degradation due to limited cold chain facilities and a lack of knowledge of sanitation among fishermen. This study aimed to analyze the sanitation conditions, handling practices, and fish storage procedures, as well as fish quality, transfer processes, and critical points of quality deterioration. Developing improvement strategies for the cold chain process in handling demersal fish. The organoleptic assessment results showed values in the range of 6.78–7.02, which showed that some fish did not meet the SNI standard (≥7.0). The main factors contributing to the decline in quality include limited ice, inadequate fish storage containers, poor sanitation, and prolonged distribution time. The identification of critical points showed that the aspects with the lowest scores were the temperature of the fish when it was unloaded from the ship (1.00), cleanliness of the fish storage area (1.14), and feasibility of the fish transport container (1.29). The SWOT analysis used to formulate a cold chain process improvement strategy resulted in an IFAS score of +1,14 and an EFAS of +0.69, which placed the strategy in Quadrant I (SO-Aggressive Strategy). The development strategy is directed towards optimizing internal strengths to take advantage of external opportunities. Recommendations include improving the efficiency and quality of the cold chain through government support, improving storage facilities, and enhancing the competence of fishermen in quality management and product diversification. Keywords: demersal fish handling, fish sanitation, critical point analysis, SWOT